Phatic Pattern Used by Teenagers in Minangkabau Society - Widya Juli Astria (Fakultas Sastra Universitas Ekasakti, 2020)
This research is to study the use of Phatic Patterns by adolescents in the Minangkabau community. In Minangkabau, the term Phatic is commonly known as stale meatballs. The use of Phatic is very commonly found in conversations by the Minangkabau people. In this study, the authors focus on the use and patterns of Phatic used by adolescents in Minangkabau in communicating. The author found that there are various Pathic Patterns used by Minangkabau teenagers in communicating expectations in Greeting, Introducing, Taking-Taking, Praise, Promises, Rejection, and Invitations. The use of Phatic is adapted to the context and the person they are talking to.